Characterization of Factor VIII Related Protein Synthesized by Human Endothelial Cell: A Study of Structure and Function - Chan, Vivian; Chan, T K (Thrombosis and Haemostasis, 1982)
Crossed immunoelectrophoresis showed that factor VIII related protein (VIII R) synthesized in the human endothelial cell (EC-VIII R) had faster electrophoretic mobility than that secreted into the culture medium (MED-VIII R). Sodium dodecyl sulphate agarose gel electrophoresis followed by radioimmunofixation showed that EC-VIII R consisted of molecules varying from 0.26 × 106 to 3.76 × 106 daltons while MED-VIII R had molecules ranging from 0.93 × 106 to greater than 10 × 106 daltons, similar to that present in plasma. The smallest VIII R molecule present in normal plasma or spent culture medium (0.93 × 106 daltons) corresponded to a tetramer of subunits of 0.22-0.24 × 106 daltons. Only molecular forms greater than 3.76 × 106 daltons possessed ristocetin cofactor activity. Sonication (15 μ. amplitued for 30 secs) effectively broke the non-covalent bonds of the VIII R multimers resulting in smaller molecules. Thus endothelial cells in culture synthesized VIII R subunits and assembled them into the higher multimeric forms on secretion. Different types of von Willebrand disease could result from defects of either of the two processes.
Keywords: Human endothelial cells; Factor VIII related protein; Multimeric forms; Ristocetin cofactor